The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0144334
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Maternal Hydration Strategies for Amniotic Fluid Improvement in Isolated Oligohydramnios and Normohydramnios: Evidence from a Systematic Review of Literature and Meta-Analysis

Abstract: ObjectiveSeveral trials aimed at evaluating the efficacy of maternal hydration (MH) in increasing amniotic-fluid-volume (AFV) in pregnancies with isolated oligohydramnios or normohydramnos have been conducted. Unfortunately, no evidences support this intervention in routine-clinical-practice. The aim of this systematic-literature-review and meta-analysis was to collect all data regarding proposed strategies and their efficacy in relation to each clinical condition for which MH-therapy was performed with the ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
3
24
0
1
Order By: Relevance
“…11 Another study conducted in 2015 by Salvatore Gizzo was also favoring our results. 7 The hypothesis of the study that "maternal oral hydration is better than routine hydration in terms of mean amniotic fluid index in third trimester oligohydramnios" is justified.…”
Section: Resultsmentioning
confidence: 99%
“…11 Another study conducted in 2015 by Salvatore Gizzo was also favoring our results. 7 The hypothesis of the study that "maternal oral hydration is better than routine hydration in terms of mean amniotic fluid index in third trimester oligohydramnios" is justified.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies from high income countries suggest that treating some cases of oligohydramnios may improve certain outcomes [13,14,23], but whether interventions such as amnioinfusion or early delivery or delivery by cesarean section would achieve similar results in LMICs is unknown [24,25]. The overall trial showed no benefit of ultrasound for any important outcome including maternal death or near- P-value from a logistic regression model for at least one oligohydramnios finding adjusting for site and maternal characteristics using general estimating equations to account for the correlation of outcomes within cluster miss maternal mortality, stillbirth and neonatal mortality [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent meta-analysis has suggested that IO in low-risk pregnancy was associated with adverse outcomes such as neonatal intensive care unit (NICU) admission, cesarean delivery, and meconium aspiration syndrome [ 7 ]. A systematic review and meta-analysis suggested that oral or intravenous maternal hydration improves amniotic fluid volume; however, further evaluation of its clinical application is required [ 8 ].…”
Section: Introductionmentioning
confidence: 99%